TRADISIONAL KE DIGITAL: ANALISIS TRANSFORMASI PENDIDIKAN ISLAM DALAM KONTEKS GLOBALISASI - Iwan Ridwan; Putri Sabrina Panggabean; May Elisa Sitompul (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
With the advancement of technology, of course there will be huge challenges that Islamic education will face. where the digital era can accompany various changes in various aspects of life, including changes in the world of education. Globalization accelerates the pace of knowledge and various kinds of news and relations between cultures,  deliver Islamic education so that it can adapt its values without losing its original values. Through the library study method and it was found that the digitalization of Islamic education, technology integration, and strengthening Islamic values is the main key in facing the dynamic global era.